Program-modeling complex BPC algorithm stream encryption and noiseless coding video signals UAV - Белецкий, Анатолий Яковлевич; Навроцкий, Денис Александрович; Свердлова, Анастасия Дмитриевна; Семенюк, Александр Иванович; Максименко, Артем Владимирович (Ukrainian Information Security Research Journal, 2015)
Stream BPC (Block Packet Cipher) algorithm is oriented to cryptographic protection and noiseless coding discrete video transmitted from the board of rolling the aircraft tothe ground. Encryption is done bitwise addition modulo 2blocks of the source text, the size of which form the 128,256, 512 or 1024 bits, with equal length blocks of binary pseudo-random numbers (keys or gammas). Flows of gamma synchronously generated both on board and onthe ground, produced a set of cryptographic transformations (primitives) secret base public key isloaded on the stage of pre-service and in groundequipment onboard encryption. Noiseless coding blocksencrypted video by one of the three algorithms:Hamming, BCH or Reed-Solomon. A plurality of blocksof data, the number of which is proportional to the sizerange of forms packet encrypted information. Forming atransition to the next packet is preceded by conversion ofthe public encryption key, which in turn controls theparameters of the key block (XOR function). Modelingcomplex is subject to exclusion or modification of one ormore primitives involved in the formation of cipheringschemes.